Australian Institute of Building papers - Australian Institute of Building (The Institute, 1989)
Contents: Project organisation: a case study; sytems approach to life cycle costing appraisal; buildings and occupant health; a construction case flow model; main guises of project manager; information network for the construction industy; trade contractor default in a construction management setting and concrete stone.